2008
DOI: 10.1007/s11999-008-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal-on-Metal Hip Arthroplasty Does Equally Well in Osteonecrosis and Osteoarthritis

Abstract: Many previous reports suggest total hip arthroplasty performs suboptimally in young patients with osteonecrosis. We retrospectively compared the performance of metal-on-metal articulation in a select group of 107 patients with 112 hips (98 uncemented and 14 cemented stems) 60 years of age or younger with either osteonecrosis (27 patients, 30 hips) or primary osteoarthritis (80 patients, 82 hips). We evaluated all patients with patient-generated Harris hip score forms and serial radiographs. Five mechanical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…During the past decade, various studies have reported outcomes and survival of alternative bearing surfaces in THA [6,7,9,12,14,15,19,20,[23][24][25]. Complications associated with the use of hard-on-hard bearings include squeaking, fracture, liner disassociation, metallosis, and hypersensitivity reactions occurring in some patients [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, various studies have reported outcomes and survival of alternative bearing surfaces in THA [6,7,9,12,14,15,19,20,[23][24][25]. Complications associated with the use of hard-on-hard bearings include squeaking, fracture, liner disassociation, metallosis, and hypersensitivity reactions occurring in some patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, the most common reason for revision THA was not bearing related, which was consistent with the previous studies reporting outcomes of COC THA. A review of recent literature reporting outcome of MOM THA demonstrated an overall survival rate between 93% and 99% [6,23] (Table 3). The failure rate of MOM THA in our cohort (5%) was similar to these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Also, plasma spray provides good early stability as a result of its high frictional interface with the adjacent bone and its closed-pore structure prevents particulate debris migration [3,13]. The metal femoral head was the Protasul Cobalt Chrome Metasul1 alloy [5,9,12]. Head diameter was 44 to 50 mm in 164 hips, 52 to 56 mm in 33 hips, and greater than 56 mm in nine hips.…”
Section: Methodsmentioning
confidence: 99%
“…Metal-on-metal articulation for THA has been one subject of research for us [5,9,12,19,23]. Our only repeatable complication with this articulation was dislocation (using 28-and 32-mm heads), so the large-diameter head was attractive [5,12,19].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the included articles were of Level IV evidence. In the MoM group, there were only two reports with Level I to II evidence [86,87] and one report with Level III evidence [18]. In the ceramic-on-ceramic group, there were two reports with Level I evidence [16,53], one report with Level II evidence [50], and two reports with Level III evidence [19,69] (Tables 1 and 2).…”
Section: Search Strategy and Criteriamentioning
confidence: 96%